(untitled) (Tribhuvan University Journal of Microbiology, 2023)
Objective: To assess the antimicrobial pattern of Escherichia coli isolates from urine samples, determine the proportion of multidrug resistant (MDR) and extended spectrum beta-lactamase (ESBL) and blaCTX-M gene of E. coli from the urine samples. Methods: A total of 2452 urine samples were collected and processed from April to October 2023 in clinically suspected urinary tract infection (UTI) patients attending B&B Hospital Pvt. Ltd to identify possible bacteria using standard microbiological procedures. E coli isolates were further subjected to antimicrobial susceptibility testing using Kirby Bauer disk diffusion method. Combination disk method was used to identify the ESBL phenotypes. Molecular detection of blaCTX-M gene was performed using conventional polymerase chain reaction. Results: A total of 338 (13.7%) samples showed significant bacterial growth. Maximum bacterial growth was found in outpatients (70.4%) and in patients above 60 years of age. Gram negative bacteria (87.8%) were predominant and E. coli (54.4%) was the most frequent. Nitrofurantoin, Aminoglycosides, Carbapenems and Polymixins were effective antibiotics. Among 184 E. coli isolates, 54 (29%) were MDR, 30 (16.3%) were ESBL producer. blaCTX-M gene was detected in 90% of the phenotypically confirmed ESBL producers. Conclusion: E. coli is the major cause of UTI and blaCTX-M is a prime contributor of ESBL production. High rate of resistance to third-generation Cephalosporins, Flouroquinolones and Cotrimoxazole make these antibiotics unsuitable for the treatment of UTI.